2012
DOI: 10.1016/j.virol.2012.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus regulatory HBx protein binding to DDB1 is required but is not sufficient for maximal HBV replication

Abstract: Robust hepatitis B virus (HBV) replication is stimulated by the regulatory HBx protein. HBx binds the cellular protein DDB1; however, the importance of this interaction for HBV replication remains unknown. We tested whether HBx binding to DDB1 was required for HBV replication using a plasmid based replication assay in HepG2 cells. Three DDB1 binding-deficient HBx point mutants (HBx69, HBx90/91, HBxR96E) failed to restore wildtype levels of replication from an HBx-deficient plasmid, which established the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 66 publications
2
67
1
Order By: Relevance
“…An intriguing speculation coming from previous reports that the HBx-DDB1 interaction is critical for viral genome replication (15,16) was that HBx-targeted host factors that restrict viral DNA replication are regulated by the Cul4-DDB1 ubiquitin E3 ligase (12). Contrary to the expectation of that hypothesis, our findings consistently indicated that the DDB1-HBx interaction is largely dispensable for HBx-stimulated viral genome replication.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…An intriguing speculation coming from previous reports that the HBx-DDB1 interaction is critical for viral genome replication (15,16) was that HBx-targeted host factors that restrict viral DNA replication are regulated by the Cul4-DDB1 ubiquitin E3 ligase (12). Contrary to the expectation of that hypothesis, our findings consistently indicated that the DDB1-HBx interaction is largely dispensable for HBx-stimulated viral genome replication.…”
Section: Discussioncontrasting
confidence: 89%
“…In line with this notion, it was reported previously that the DDB1-HBx interaction imparts HBx-induced genetic instability and HBx-induced S-phase progression, potentially contributing to hepatocellular carcinoma development (8,13,14). Moreover, the DDB1-HBx interaction was shown to be essential for the ability of HBx to stimulate viral genome replication in an experiment carried out in HepG2 cells, a hepatoma cell line (15,16).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…This is an attractive idea, because DDB1 is a known DNA-binding protein. HBx mutant proteins that do not bind DDB1 are unable to restore HBx-deficient replication in the HBV plasmid replication assay, and the defect occurs at the level of viral transcription (Leupin et al 2005;Hodgson et al 2012).…”
Section: Hbx and Cccdnamentioning
confidence: 99%